Are neurocognitive abilities and social cognition related to social and role functioning in familial high risk group for psychosis - PERDAHLI FİŞ, NEŞE (My University, 2022)
Aims In this study, we aimed to compare neurocognitive abilities and social cognitive features among adolescent offspring of psychotic individuals and healthy controls. Methods The study sample was composed of offspring of patients with psychotic disorders (n = 30), the high risk group (HR), and age and sex matched healthy controls (n = 32) the Control Group (CG). The psychiatric diagnoses were established by using the KD-SADS. Strengths and Difficulties Questionnaire adolescent and parent forms (SDQ-A, SDQ-P) were used. General functioning status were evaluated by The Children\"s Global Assessment Scale (CGAS) and Global Functioning Scale: Social and Role Functioning. Wisconsin Cart Sorting Test, Controlled Oral Word Association Test, California Verbal Learning Test, Stroop Colour and Word Test and Trail Making Tests A and B were used to assess neurocognitive abilities; to assess social cognition and empathy skills DANVA-2 and Bryant Empathy Scale were used, respectively. Results Among HR 53.33% had at least one psychopathology. SDQ-A, SDQ-P scores were significantly higher, and CGAS, social and role functioning scores were significantly lower in HR. Neurocognitive test scores were significantly worse except for SCWT scores in the HR. No significant differences were obtained in social cognition. A variety of the neurocognitive abilities were significantly correlated with the role functioning. In regression analyses, the most predictive scores were WCST total correct scores and role functioning score. Conclusions HR group showed more impairments in neurocognition, social, role and overall functioning, whereas there was no significant difference in terms of social cognition. Disturbances in neurocognition were correlated with impairments in role functioning.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psychiatric Mental Health; Psychiatry and Mental Health; family high risk; neurocognition; psychosis; social cognition; CLINICAL HIGH-RISK; UNAFFECTED 1ST-DEGREE RELATIVES; BIPOLAR DISORDER; DIFFICULTIES QUESTIONNAIRE; 1ST-EPISODE PSYCHOSIS; GENETIC VULNERABILITY; YOUNG-ADULTS; SCHIZOPHRENIA; ATTENTION; INDIVIDUALS